A mobilidade académica e a emigração portuguesa qualificada - Rui Machado Gomes (Investigação, 2019)
In this book individual options of mobility are described and analyzed they as part of a long history that has been written for centuries by many Portuguese emigrants of different generations and qualifications. The difficulties of today are lessened, the biographic stories are, as a rule, successful and reveal people who have found a way forward. The same individual options, however, are also the expression that a deep evil attacks Europe, making the most skilled in the peripheral countries attracted to the central countries, where resources are available, leaving the least developed countries economy without knowledge and innovation. It resonates in the murmur of the voices of those we hear an experience that longs to be shared and understood in its fullness.